Pengaruh Profitabilitas, Ukuran Perusahaan, dan Arus Kas Bebas Terhadap Kebijakan Dividen - Pradnyavita, Kadek Indri; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 30 No 1 (2020)DO - 10.24843/EJA.2020.v30.i01.p18, 2020)
The company is faced with the decision to distribute dividends to shareholders or withhold earnings for reinvestment activities. The purpose of this study was to determine the effect of profitability, company size and free cash flow on dividend policy. This study took a sample of manufacturing companies listed on the Indonesia Stock Exchange in the period 2016-2018. The sampling technique used was purposive sampling, so as many as 13 companies were obtained. The total sample taken for 3 years was 39 observations. The technique used in this research is multiple linear regression analysis. Based on the results of the analysis of this study proves that profitability, company size, and free cash flow affect positive dividend policy. Keywords: Profitability; Company Size; Free Cash Flow; Dividend Policy